2014
DOI: 10.1016/j.enbuild.2014.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of a solid oxide fuel cell cogeneration/trigeneration system for hotels in Hong Kong

Abstract: Solid oxide fuel cell (SOFC) is promising for efficient stationary power generation. The high temperature waste heat from SOFC stack can be recovered for cogeneration/trigeneration.Due to the lack of relevant analysis on SOFC system in Hong Kong, this research is purposely designed to investigate the economics of a SOFC-absorption cooling cogeneration/trigeneration system for building application in Hong Kong. Energy consumption profile of Hotel ICON is adopted for a case study. Existing products of SOFC serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 17 publications
(17 reference statements)
0
29
0
Order By: Relevance
“…The initial cost of one-stage chiller products is $92,000 according to [23], while the two-stage chiller products are slighter higher (30%). Thus, the SOFC subsystem's initial costs including LiBr-H 2 O absorption central air conditioning is $120,000, in addition to a water-heating unit ($100,000) [11]. Furthermore, the costs of auxiliary components (e.g., transformers, exhaust-flow controllers, etc.)…”
Section: Capex and Opex Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The initial cost of one-stage chiller products is $92,000 according to [23], while the two-stage chiller products are slighter higher (30%). Thus, the SOFC subsystem's initial costs including LiBr-H 2 O absorption central air conditioning is $120,000, in addition to a water-heating unit ($100,000) [11]. Furthermore, the costs of auxiliary components (e.g., transformers, exhaust-flow controllers, etc.)…”
Section: Capex and Opex Analysismentioning
confidence: 99%
“…A SOFC is an electrochemical-conversion DER device that produces electricity directly from a highly efficient and eco-friendly process of fuel oxidation, and has high fuel-flexibility, high energy efficiency, low environmental impact, and a long lifespan [7][8][9]. Prior research has found biogas to have great potential as fuel for SOFCs, with energy efficiency of 55-65% or better [10], and that SOFC-based multi-generation systems can achieve higher efficiency (72-90%) than traditional thermal power generators (35-45%) [11], in addition to reducing the emission of greenhouse gases (GHGs) and gaseous pollutants (e.g., NO x and SO 2 ) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous studies [51][52][53][54][55][56][57][58], which assessed the economic and environmental effects of the FC system, it was determined that there were complex correlations among the key factors affecting the energy performance of the FC system. As shown in Table 1, these key factors mostly consist of system factors.…”
Section: Selecting Key Factors Affecting System Performances Of the Fmentioning
confidence: 99%
“…First, the economic effects of the fuel cell system were analyzed under various conditions [55][56][57][58][59][60][61]. Mahlia et al [55] assessed the economic effect of a 1 kW PEMFC system for a household in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%